2008
DOI: 10.1371/journal.ppat.1000040
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Chitin Synthesis Rescues Candida albicans from Echinocandins

Abstract: Echinocandins are a new generation of novel antifungal agent that inhibit cell wall β(1,3)-glucan synthesis and are normally cidal for the human pathogen Candida albicans. Treatment of C. albicans with low levels of echinocandins stimulated chitin synthase (CHS) gene expression, increased Chs activity, elevated chitin content and reduced efficacy of these drugs. Elevation of chitin synthesis was mediated via the PKC, HOG, and Ca2+-calcineurin signalling pathways. Stimulation of Chs2p and Chs8p by activators of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

30
439
0
9

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 370 publications
(478 citation statements)
references
References 61 publications
30
439
0
9
Order By: Relevance
“…Calcium signalling through the Ca 2+ -binding protein calmodulin and the Ca 2+ -calmodulin-dependent phosphatase calcineurin has been implicated in a multitude of processes, including stress response, mating, budding, and actin-based processes (Cyert, 2001) as well as in determining tolerance to antifungal drugs (Cruz et al, 2002;Del Poeta et al, 2000;Kontoyiannis et al, 2003;Sanglard et al, 2003;Steinbach et al, 2007;Walker et al, 2008). Cellular calcium levels in S. cerevisiae are regulated by multiple channels and transporters, including the voltage-gated high-affinity calcium channel Cch1 which functions together with the stretch-activated cation channel Mid1 (Locke et al, 2000).…”
Section: The Calcium/calcineurin Signalling Pathwaymentioning
confidence: 99%
“…Calcium signalling through the Ca 2+ -binding protein calmodulin and the Ca 2+ -calmodulin-dependent phosphatase calcineurin has been implicated in a multitude of processes, including stress response, mating, budding, and actin-based processes (Cyert, 2001) as well as in determining tolerance to antifungal drugs (Cruz et al, 2002;Del Poeta et al, 2000;Kontoyiannis et al, 2003;Sanglard et al, 2003;Steinbach et al, 2007;Walker et al, 2008). Cellular calcium levels in S. cerevisiae are regulated by multiple channels and transporters, including the voltage-gated high-affinity calcium channel Cch1 which functions together with the stretch-activated cation channel Mid1 (Locke et al, 2000).…”
Section: The Calcium/calcineurin Signalling Pathwaymentioning
confidence: 99%
“…Contribution of the Inp51-Irs4 PI(4,5)P2 regulatory complex and the Cek1-MAPK and Ras-cAMP hyphal regulatory pathways to paradoxical growth. Activation of the PKC-Mkc1 cell wall integrity signaling pathway also has been shown to contribute to paradoxical growth (17,27,28), at least in part by coordinately regulating chitin synthesis in conjunction with the calcineurin pathway. In previous studies, we demonstrated that independent disruptions of the PI(4,5)P2 5Ј-phosphatase Inp51 and its interacting EH-domain protein Irs4p resulted in elevated PI(4,5)P2 levels, overactivation of the PKC-Mkc1 pathway in response to cell wall stress, and hypersusceptibility to caspofungin (1,2).…”
mentioning
confidence: 99%
“…In the case described by Costa-de-Oliveira et al (2011), the C. glabrata strain had a mutation in the FKS region but the chitin content was unspecified. Understanding the mechanisms of resistance will help promote further research into chitin synthase inhibitors which are known to act synergistically with the echinocandins (Walker et al, 2008). To our knowledge, this is the first report of a Candida isolated from bloodstream with both FKS mutation and altered cell wall chitin content.…”
Section: Discussionmentioning
confidence: 86%
“…Mutations in the FKS2 gene have also been reported in Candida glabrata and Candida guilliermondii. In contrast to the FKS1 mutations, the compensatory rise in chitin synthesis is related to the cell wall salvage pathway involving protein kinase C (PKC) signalling (Walker et al, 2008). The compensatory mechanism of the chitin-rescue phenomenon is not yet fully understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation